BEAT THE DECAY IN A FOODY FASHION - KEERTHI VENKATESAN,; MANISH RANJAN, (International Journal of Pharma and Bio Sciences, 2015)
Dental caries commonly referred to as tooth decay is a dynamic, progressive, infectious, diet-dependent and most prevalent chronic disease with a global distribution. Individuals of any age are susceptible to this disease at any point of time throughout their life. This disease is reversible if detected at the earliest possible stage. Dental caries can be the outcome when pathological factors leading to demineralization exceeds the protective factors leading to remineralization. Research is still being carried out to increase the caries resistance of teeth and to reduce the risk of cariogenic bacteria. This review focuses on various naturally occurring products which includes green tea, cranberry, coffee, chocolate and probiotics which are anticariogenic nutritionally.